Pembentukan Self Efficacy Mahasiswa PGRA dan Dampaknya bagi Teacher Efficacy Alumni Pendidikan Guru Raudlatul Athfal (Study Literasi & Survey terhadap Alumni PGRA di Yogyakarta) - Faizah, Umi (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
Self-efficacy is the belief that encourages individuals to do and achievesomething, that is, as a multi-purpose instrument for this concept not only relatesto the ability, but also able to gain confidence that the individual can do variousthings in various conditions. They have been many studies that reveal about theimportance of self-efficacy in a variety of different areas. This study seeks to exploreliteracy in theory of self-efficacy and equip it with the data surveyed alumni inteaching activities in early childhood / kindergarten / RA / BA. Conclusions tobe drawn from this study that the formation of Self-efficacy when they becomestudents has positive impact on Teacher Efficacy alumni PGRA as evidenced by a100% pass at the time of follow UKG (Teacher Competency Test) 2014.